2016
DOI: 10.2147/jpr.s105284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pedicle fixation combined with 125I seed implantation for metastatic thoracolumbar tumors

Abstract: PurposeThe aim of this study was to investigate the clinical efficacy of pedicle fixation combined with 125I brachytherapy in treating metastatic thoracolumbar tumors.Patients and methodsA retrospective analysis of the clinical data of seven metastatic thoracolumbar tumor patients who received pedicle fixation combined with radioactive 125I seed implantation brachytherapy in our department between January 2009 and December 2013 was performed. The visual analog scale (VAS) for pain and the Karnofsky performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…Decompressive surgery combining with precise 125 I brachytherapy seed implantation facilitates rapid decompression, immediate metastatic radiation, and accurate tumor assessment, which has become a new modality for MESCC patients. 12 , 13 Rogers et al 13 reported that surgical resection and 125 I brachytherapy was well tolerated and resulted in durable local control and ambulatory function outcome in patients with MESCC. Thirty patients were included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Decompressive surgery combining with precise 125 I brachytherapy seed implantation facilitates rapid decompression, immediate metastatic radiation, and accurate tumor assessment, which has become a new modality for MESCC patients. 12 , 13 Rogers et al 13 reported that surgical resection and 125 I brachytherapy was well tolerated and resulted in durable local control and ambulatory function outcome in patients with MESCC. Thirty patients were included in the study.…”
Section: Discussionmentioning
confidence: 99%
“…The morbidity was restricted to 4 postoperative events. Qian et al 12 concluded that pedicle fixation combined with 125 I brachytherapy could effectively relieve short-term pain and improve patient’s quality of life after retrospectively analyzing seven metastatic thoracolumbar tumor patients. However, the available studies were subject to small retrospectively samples, simple observations, and indistinct endpoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, a systematic review was published, which summarized the role of the treatment modality in painful spinal metastases [82]. Seven studies (which analysed treatment efficacy on pain control) reported a decrease of pain intensity after brachytherapy [83,84,85,86,87,88,89] (Table 4).…”
Section: Brachytherapy For the Treatment Of Painful Bone Metastasesmentioning
confidence: 99%
“…In recent years, 125 I-seed implantation has been found to show very good therapeutic effects on malignant liver tumors 1. However, this treatment is always obscured by the costa and lung tissue, and displacement of the liver caused by breathing also makes treatment difficult.…”
Section: Introductionmentioning
confidence: 99%